AKIBAT HUKUM TERHADAP PERATURAN DESA YANG MENGANDUNG CACAT FORMIL DAN MATERIL DALAM PROSEDUR PEMBUATANYA - Oktarina, Evi (Justici, 2024)
Abstract Village regulations are formed in the framework of implementing village government, thus village regulations must be a further elaboration of higher statutory regulations and must not conflict with public interests and/or higher statutory regulations, and must pay attention to socio-cultural conditions of local village communities, in an effort to achieve long-term, medium-term and short-term goals of government, development and community services. The problem that the author addresses in this article is the legal consequences of village regulations that contain formal and material defects in the procedures for making them. Legal Consequences of Village Regulations that contain formal and material defects in the procedures for making Village Regulations can be canceled if they do not fulfill the material content of a statutory regulation